Clinical and diagnostic insights into Brucella spondylitis: a comprehensive retrospective study - Feng, Qiangsheng; Ha, Xiaoqin; Yuan, Xing; Qiu, Xiaoming; Fang, Jing; Song, Yuejuan (Frontiers in Immunology, 2025)
BackgroundThis study evaluates the diagnostic value of etiological and serological testing and the clinical characteristics of spine brucellosis.MethodsA retrospective analysis was conducted on 200 cases of spine brucellosis diagnosed between 2012 and 2025, alongside 200 non-infected controls. Bacterial cultures, clinical features, serological results (Standard Agglutination Test [SAT] and Rose Bengal Test [RBT]), and imaging findings were analyzed.ResultsAmong 200 patients with spinal involvement, Brucella melitensis was confirmed via bacterial culture in 29 cases (14.5%), with spinal tissue culture demonstrating the highest diagnostic yield (58.6%, 17/29) and a median detection time of 3 days. Spinal brucellosis constituted 25% of all brucellosis cases, exhibiting a male predominance (76.5%) and a mean patient age of 52.2 ± 10.1 years. The median hospital stay was 14.7 ± 7.8 days, while the median duration of chronic spinal brucellosis was 4.4 months (IQR: 1.5–11.5). The lumbar spine was the most frequently involved site (78.3%), followed by the cervical (8.6%) and thoracic (5.1%) regions. CT imaging revealed characteristic lesions, including bone destruction (53.0%), intervertebral space stenosis (38.5%), disc herniation (22.0%), degenerative changes (4.5%), and osteomyelitis (1.0%). Diagnostic sensitivity varied significantly across methods: blood culture (48.0%, 12/25), lumbar tissue culture (65.4%, 17/26), SAT(91.3%, 157/172), and RBT(95.9%, 165/172). Notably, all 15 serologically false-negative cases (7 by RBT and 15 by SAT) occurred in male patients. ROC curve analysis identified C-reactive protein (CRP) as a robust biomarker, with a cutoff of 1.21 mg/L yielding 85.2% sensitivity and 71.7% specificity (Z = 6.167, p < 0.001). Multivariable regression identified female sex (OR = 2.44, 95% CI: 1.20–4.96) and lumbar involvement (OR = 1.61, 95% CI: 0.75–3.46) as independent predictors of chronicity (p < 0.05). All patients received standard 3-month combination therapy with doxycycline and rifampicin, with surgical intervention required in 45.5% (91/200) of cases. Clinical outcomes were favorable across the cohort, with rare reports of severe complications.ConclusionsBrucella Spondylitis, typically chronic and lumbar-predominant, presents with bone destruction, gap stenosis, and disc herniation on imaging. Diagnosis relies on lumbar tissue culture, SAT, RBT, and CT. Early diagnosis and combined medical-surgical management improve outcomes.